MASTERING VEEAM BACKUP & REPLICATION 10 : protect your virtual environment and implement cloud... backup using veeam technology. - CHILDERHOSE, CHRIS (PACKT PUBLISHING LIMITED, 2021)
Veeam is an infrastructure backup solution for VMware vSphere or Hyper-V to enable VM and server backup. This book takes you through installation best practices, optimizations, and the 3-2-1 rule, before going on to examine repository and proxy-related topics and finally advanced topics such as DataLabs, Instant VM Recovery, and Veeam ONE.
Keywords: VMware vSphere.; VMware vSphere; COMPUTERS / Security / Networking.; Networking.; Servers.; Databases.; COMPUTERS.; Security.; Virtualization.; Operating Systems.